(untitled) (Bangladesh Journal of Zoology, 2026)
Dengue poses a serious threat to many countries, including Bangladesh. Aedes aegypti and Aedes albopictus are the major vectors of dengue disease. This study was carried out to evaluate three types of passive Ovitraps (INZECTO Mosquito trap, Gravitrap and BG-GAT) to determine their effectiveness in reducing dengue burden in Bangladesh and to find out the preferred egg laying habitat of Aedes albopictus. Four INZECTO Mosquito traps, one Gravitrap and one BG-GAT were deployed, where Gravitrap and BG-GAT target adult mosquitoes and INZECTO Mosquito trap targets larvae. Four Inzecto mosquito traps were placed in different vegetative environments to identify egg-laying habitats of Aedes albopictus. Larvae were collected from the INZECTO trap weekly, and adults were gathered from the Gravitrap and BG-GAT twice a week. For testing IGRs like Pyriproxyfen, larvae were collected after twelve days. The mean larval densities from the INZECTO mosquito traps were 12.125, 26.375, 19.375 and 59.5. Result showed that Aedes albopictus preferred laying eggs in dense vegetation with large trees and tall grasses, with the highest larvae count of 59.5. A significant positive relationship (p<.001) existed between dense vegetation and larval numbers. The result indicated that Pyriproxyfen prevented larvae from maturing into adults. The average adult capture density was 3±0.31 for BG-GAT and 5±0.41 for Gravitrap, with Gravitrap being 1.7 times more efficient in terms of adult capturing. Mosquitoes favored laying eggs in ground traps over those in trees. Gravitrap and Inzecto mosquito trap are more effective than BG-GAT. By leveraging larval Inzecto trap and adult Gravitrap for both surveillance and regular monitoring of the vector population can help in predicting dengue outbreaks in Bangladesh. Bangladesh J. Zool. 53(3): 311-320, 2025